Detoxification and methane production kinetics from three‐phase olive mill wastewater using Fenton's reagent followed by anaerobic digestion. Issue 1 (10th September 2018) - Bampalioutas, Konstantinos; Vlysidis, Anestis; Lyberatos, Gerasimos; Vlyssides, Apostolos
Abstract: BACKGROUND: The implementation of an integrated treatment scheme consisting of an oxidation and an anaerobic digestion (AD) process was investigated at laboratory scale for the detoxification of olive mill wastewaters (OMWW) and their utilization for energy production. Initially, a detoxification step was implemented for oxidizing the OMWW in a batch‐stirred reactor with Fenton's reagent. Subsequently, the pretreated OMWW was fed to an anaerobic digester containing active sludge in order to determine its suitability for further biological treatment and biogas production. RESULTS: The kinetics of the two processes were examined for different initial conditions by varying the most important parameters: the initial concentrations of H2 O2 and FeSO4 .7H2 O and the temperature of the oxidation process while the initial pH was kept constant. Increasing the initial concentrations of H2 O2 and FeSO4 .7H2 O from 1 to 5 g L −1 and temperature from 20 to 35 °C, led to increased total phenolic content (TPC) removal (88.8%) and TOC degradation (35.4%) in the chemical oxidation process and an increased pseudo‐first‐order constant value (kAD  = 0.718 d −1 ) in the AD process. The optimum k AD value corresponded to a biomethane production of 20.1 L CH4 / L pretreated OMWW. A modified pseudo‐first order model was selected to describe the conducted experiments. CONCLUSION: The combination of Fenton's oxidation together with AD is an effective method for treating three‐phase OMWW as the TPC is first significantly decreased and then substrate biodegradability is enhanced as the proposed pretreatment methodology increases considerably the rate of AD. © 2018 Society of Chemical Industry